Feasibility Analysis of a Public Street Lighting Project Based on Solar Power Plant in Jerambah Gantung, Pangkalpinang City - Rehan; Ega Mawarni; Muhammad Sholehudin; zalva; M. Afdal Samsuddin (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2024)
Solar Public Street Lighting refers to a public street lighting system that uses electrical power from solar energy. In this system, the lights are powered independently by energy generated from sunlight, which is collected through solar panels or solar cells, and then converted into electricity through the photovoltaic process. The advantages of solar street lighting are energy-efficient and have high durability. This study aims to evaluate the planning of solar-based public street lighting in the Jerambah Gantung area, Pangkalpinang City. Currently, along the Jerambah Gantung road in Pangkalpinang City, there is no public street lighting system, although the road is often used by residents of Balunijuk Village as an access point to Pangkalpinang City. To consider the safety aspects of road users, it is necessary to plan public street lighting that utilizes energy from renewable sources, namely solar energy. Keywords: Lighting, Street Light, Solar Panel